The changing world of banking - Prochnow, Herbert Victor, Jr.; Prochnow, Herbert V. (New York : Harper & Row, 1973)
The objective of the book is to achieve a practical need for a one-volume study of actual American banking practices which reflects the vast changes of recent years. This study will be helpful to bankers and corporate treasures in their understanding of the operations of modern banking and also to those members of university and college faculties who are interested in banking, finance, and economics.
Includes bibliographical references and index.
rpm 30/04/2018
Loans
Keywords: Banks and banking; Bank management